2019
DOI: 10.1021/acsomega.9b02117
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Surface Pt-Rich Bimetallic AuPt Nanocatalysts for Selective Hydrogenation Reactions

Abstract: Bimetallic nanocatalysts, with efficient and controllable catalytic performance, have a promising application in chemical production. In this study, surface Pt-rich bimetallic AuPt nanoparticles with different Pt/Au ratios were prepared and tested in selective hydrogenation reactions of substituted nitroaromatics. Au nanoparticles were first prepared with n-butyllithium as a rapid reducer, which were further used as seeds in the slow growth process of Pt atoms. Because of the employed sequential reduction meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Peng et al [19] showed that the deposition of Pt-submonolayers on AuNPs and the Pt coverage-dependent electrocatalytic activity for MOR, also revealed that the low Pt coverage such as monoatomic-thick layers exhibited remarkably higher electrocatalytic performance and structural stability, whereas at higher Pt-shell thickness there was not any obvious increment found in the electrocatalytic activity. The surface Pt-rich bimetallic nanocatalysts with different Au/Pt atomic ratios have demonstrated enhanced hydrogenation selectivity or activity than AuPt alloys and monometallic Pt nanomaterials [20,21]. In addition, Au@Pt NPs showed the highest response current for the catalytic oxidation of glucose solution compared with those of Pt and Au NPs [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al [19] showed that the deposition of Pt-submonolayers on AuNPs and the Pt coverage-dependent electrocatalytic activity for MOR, also revealed that the low Pt coverage such as monoatomic-thick layers exhibited remarkably higher electrocatalytic performance and structural stability, whereas at higher Pt-shell thickness there was not any obvious increment found in the electrocatalytic activity. The surface Pt-rich bimetallic nanocatalysts with different Au/Pt atomic ratios have demonstrated enhanced hydrogenation selectivity or activity than AuPt alloys and monometallic Pt nanomaterials [20,21]. In addition, Au@Pt NPs showed the highest response current for the catalytic oxidation of glucose solution compared with those of Pt and Au NPs [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It generally gives pure particles. Wang et al prepared CuÀ Co bimetallic nanoparticles by reducing their layered double hydroxide (LDH) precursors in 10% H 2 /Ar atmosphere at 300 °C for 4 h. [27] The LDH precursors were [25] , Copyright (2019), with permission from American Chemical Society. (b) IrÀ M/Al 2 O 3 catalysts for the reduction of nitroarenes.…”
Section: Preparation Techniques For Bimetallic Nanoparticlesmentioning
confidence: 99%
“…Shao and co-workers synthesized alloyed AuÀ Pt/Al 2 O 3 and used it for hydrogenation of nitroarenes. [25] The homogeneous catalysts were prepared via co-reduction [20] Reproduced with permission from ref. [20].…”
Section: Preparation Techniques For Bimetallic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The native ligand 1, 3-thiazolidine-4-ones is used to inhibit polo-like kinase 1 enzyme for the uncontrolled growth of cell division into cancer [13]. Metallic nanocatalysts have played a vital role in the chemical industry; optimizing their catalytic activity enables signi cant cost reduction [14]. Due to the extraordinary features of nanoparticles, such as optical, catalytic, and electric capabilities that may be adjusted depending on the particle's size, size distribution, and morphology [15], nanoparticles have been extensively explored.…”
Section: Introductionmentioning
confidence: 99%